Diagnostic Accuracy of Contrast Enhanced Computed Tomography Scan in Characterizing the Adrenal Masses as Adenomas or Non-Adenomas by Taking Histopathology as a Gold Standard - Qurat-ul-Ain; Nayab, Seema; Mohammd Mohsan; Mirani, Kainat; Majeed, Bushra; Faiz, Quratulain (Indus Journal of Bioscience Research, 2025)
Background: Adrenal masses are a source of diagnostic challenge with distinction of adenomas from non-adenomatous masses serving to guide management. Although readily available and well established as a tool of first choice is contrast-enhanced computed tomography, its sensitivity and specificity compared to histopathological examination require reassessment. Objective: To determine the diagnostic accuracy of contrast-enhanced CT in characterizing the adrenal masses as adenomas or non-adenomas by taking histopathology as gold standard. Study Design: Cross-sectional validation study. Duration and Place of Study: The study was conducted between March 2024 and August 2024 in the Department of Radiology, Liaquat University of Medical and Health Sciences, Jamshoro. Methodology: A total of 118 patients aged 20–85 years with adrenal masses >1 cm and attenuation values above 10 Hounsfield units on unenhanced computed tomography were enrolled. Contrast-enhanced computed tomography was performed 60 seconds after intravenous contrast administration and interpreted by a senior radiologist. Imaging findings were compared with histopathology, which served as the reference standard. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated. Results: The mean patient age was 51.13 ± 11.63 years, with females comprising 65.3% of the cohort. Computed tomography demonstrated a sensitivity of 86.7%, specificity of 93.2%, positive predictive value of 65.0%, negative predictive value of 98.0%, and overall diagnostic accuracy of 92.4%. Stratified analyses confirmed consistent diagnostic performance across gender and body mass index groups. Conclusion: Contrast-enhanced computed tomography is a reliable and effective diagnostic modality for evaluating adrenal masses, with high specificity and accuracy when compared with histopathology.